2020
DOI: 10.1021/acsaem.0c00905
|View full text |Cite
|
Sign up to set email alerts
|

Toward Moisture-Stable and Dendrite-Free Garnet-Type Solid-State Electrolytes

Abstract: All-solid-state batteries using garnet-type solid-state electrolytes (SSEs) are promising candidates for safe, high energy density batteries due to their wide electrochemical stability window, high lithium-ion conductivity at room temperature, and the use of a lithium metal anode. However, garnet-type SSEs exhibit formidable challenges, including their instability in a moisture-containing atmosphere, high interfacial resistance, and the formation of lithium dendrites. Though several strategies have been deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…), [ 24 ] and inorganic thin films (BN, ZnO, Al 2 O 3 , Cu 3 N, SnN x , Ge, Sn, Mg, C, Au, Ag, etc.) [ 25,26 ] have been utilized to optimize the Li | garnet SSE interface. Although polymer‐based buffer layers are flexible and soft and enable intimate contact with garnet SSEs, their Li‐ion conductivity at room temperature is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…), [ 24 ] and inorganic thin films (BN, ZnO, Al 2 O 3 , Cu 3 N, SnN x , Ge, Sn, Mg, C, Au, Ag, etc.) [ 25,26 ] have been utilized to optimize the Li | garnet SSE interface. Although polymer‐based buffer layers are flexible and soft and enable intimate contact with garnet SSEs, their Li‐ion conductivity at room temperature is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies found the hydrophobicity of h-BN whose contact angle was 125 effectively resisted the contact between moisture and LLZT. 91 Similar to h-BN, Li 3 PO 4 (LPO) was served as a protective layer on garnet SSEs. 92 In this work, air-stable LPO not only improved Li + conductivity of the grain boundaries and mechanical strength, but also generated an electron-insulating Li-ion conductive LPO-derived interface between the SSE and Li.…”
Section: Perovskitementioning
confidence: 99%
“…90 Copyright 2021, Elsevier); (E) concept graph of air-stable mechanism of garnet@h-BN (Reproduced with permission. 91 Copyright 2020, American Chemical Society); (F) concept graph of air-stable and Li freedendrite mechanism of garnet@LPO (Reproduced with permission. 92 Copyright 2020, Wiley-VCH) Liang et al 57 reported doping of Sn 4+ replacing Ge and P to synthesize Li 4 SnS 4 and Li 4 Sn x As y S 4 .…”
Section: Sulfide-based Ssesmentioning
confidence: 99%
See 2 more Smart Citations